2018
DOI: 10.1016/j.marpolbul.2017.06.075
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Mediterranean seagrasses with Sentinel-2 imagery

Abstract: Mediterranean seagrasses have been hailed for their numerous ecosystem services, yet they are undergoing a decline in their coverage. The major complication with resolving this tendency is the sparsity of data on their overall distribution. This study addresses the suitability of the recently launched Sentinel-2 satellite for mapping the distribution of Mediterranean seagrass meadows. A comprehensive methodology is presented which applies atmospheric and analytical water column corrections and compares the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 149 publications
(129 citation statements)
references
References 40 publications
5
119
1
4
Order By: Relevance
“…On the other hand, previously published SDB results using Sentinel-2 in the validation site of the Thermaikos [31] with the original Traganos17 algorithm tuned in the same waters at depths between 0 and 20 m explained 1.76 times better the variation, with a 1.19-m smaller RMSE in comparison to the present Traganos17 results. In yet another SDB application in the Thermaikos site [34] with 5-m RapidEye imagery, the use of Dierssen03 empirical ratio exhibited a 0.49 lower R 2 with a decreased RMSE of 0.09 m in comparison to the herein validated Dierrsen03 model.…”
Section: Cloud-based Sdb and Model Performancecontrasting
confidence: 82%
See 3 more Smart Citations
“…On the other hand, previously published SDB results using Sentinel-2 in the validation site of the Thermaikos [31] with the original Traganos17 algorithm tuned in the same waters at depths between 0 and 20 m explained 1.76 times better the variation, with a 1.19-m smaller RMSE in comparison to the present Traganos17 results. In yet another SDB application in the Thermaikos site [34] with 5-m RapidEye imagery, the use of Dierssen03 empirical ratio exhibited a 0.49 lower R 2 with a decreased RMSE of 0.09 m in comparison to the herein validated Dierrsen03 model.…”
Section: Cloud-based Sdb and Model Performancecontrasting
confidence: 82%
“…The second and third selected approaches follow two modifications of the proposal by [30]-hereafter referred to as modified Stumpf03 and Traganos17 (after its first use in [31]), respectively-concerning the empirical relationship between the ratio of the log-transformed green band to the log-transformed blue band and water depth. The modified Stumpf03 is simply the multiplicative inverse of the original ratio; it employs the blue to green ratio instead of the original green to blue ratio:…”
Section: Empirical Satellite-derived Bathymetries (Sdb)mentioning
confidence: 99%
See 2 more Smart Citations
“…Further trials showed that close to the coastline the remote sensing reflectance of B3 (i.e., R rs (B3) green band) is greater than the equivalent reflectance of B2 (blue band) and B4 (red band). This fact revealed the existence of subsurface meadows at depths of approximately 0-8 m, which mainly consist of species such as Posidonia oceanica and Cymodocea nodosa, the latter being characteristic species of the marine flora in the study area [22]. An unsupervised classification methodology was then adopted in order to model bathymetry over various seabed compositions and by implementing as criteria the main IOPs and AOPs (i.e., the total backscattering coefficient, the total absorption coefficient, and the diffuse attenuation coefficient (K d )).…”
Section: Band Ratio Methodologymentioning
confidence: 87%